Perceptions of Animal Welfare With a Special Focus on Turkeys - Bir, Courtney; Davis, Melissa; Widmar, Nicole; Zuelly, Stacy; Erasmus, Marisa (Frontiers in Veterinary Science, 2019)
Meat consumption and public concern for farm animal welfare are increasing, despite limited public understanding of agriculture and animal welfare. Turkey is important in U.S. holiday meal traditions and turkey meat is a frequently consumed processed product (i.e. lunchmeat). However, little is known about public perceptions and knowledge of commercial turkeys. An online survey was administered to 1,695 respondents in November 2018 to examine U.S. 1) demographic factors affecting meat consumption, selection of labeled meat products, and concern for animal welfare, 2) public knowledge of turkeys and 3) concerns regarding the welfare of turkeys and other species. A total of 95% of respondents consumed meat and 10% hunted for some of the meat they consumed. Meat consumption frequency depended on region of residence, income level, gender, age, and whether respondents hunted. Of the meat consumers, 86% purchased turkey products. More meat consumers looked for the USDA organic label (39%) and the Non Genetically Modified Organism (GMO) project label (38%) than animal-welfare food labels (14%) when buying meat products. More pet owners (39%) than non-pet owners (25%) looked for animal welfare food labels. Being a pet owner increased the probability of being concerned about farm animal welfare. Concern for the commercial turkey was similar to concern for other farm animal species; self-reported knowledge of turkey production was low (mean score 2.64; scale of 1 to 7, 7=highest). Turkey welfare concerns (mean score; rank from 1-5; 5=least concerning) included poor nutrition (2.471) and illness (2.508), followed by housing (2.732), hot or cold weather (3.308) and transportation (3.981). Turkey welfare attributes that respondents cared the most about (mean score; scale of 1-5, 5=cared the least) included space to move around (2.366), followed by veterinary health and wellness (2.680), ability to perform natural behavior (2.812), no feather loss or visible injuries (3.304), and decreased aggression (3.837). Demographic factors are important determinants of meat consumption and animal welfare concern. Public knowledge of turkey production is limited, despite a large percentage of the population purchasing turkey products.